The psychological impacts of post-bariatric patients: a literature review (Research, Society and Development, 2021)
Obesity is a serious chronic disease whose main characteristic is the exaggerated accumulation of body fat which, according to the WHO, is responsible for the health impairment of approximately 4 million individuals. The objectives of the study are to analyze the psychological aspects of patients undergoing bariatric surgery, in addition to relating the adherence behavior of post-bariatric patients to the indications of the multidisciplinary team and thus categorize the possible factors that cause weight regain in post-bariatric patients. bariatric. This is an integrative literature review type research, developed with the collection of articles in online databases: Scientific and Technical Literature of Latin America and the Caribbean (LILACS), Online System for Search and Analysis of Medical Literature (MEDLINE) and in electronic database Scientific Electronic Library Online (SCIELO), through the descriptors: “Bariatric Surgery” (Bariatric Surgery) and “Mental Health” (Mental Health) and “Post-bariatric disorders” (Post-bariatric Disorders), associated with the Boolean operator AND. . Data were collected in August 2021. 123 original articles available in full, in Portuguese and English from 2016 to 2021, were analyzed in the research. 106 articles were excluded for not being within the publication period of up to 5 years, that were beyond the focus of this review, and those that did not meet the inclusion criteria. The final sample consisted of 15 publications. The results showed that anxiety and fear are the most reported pisocological aspects and that regular multiprofessional follow-up after bariatric surgery is associated with better surgical results.